2001
DOI: 10.1111/j.1530-0277.2001.tb02336.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum IgE in Alcoholics: Relationship With Th1/Th2 Cytokine Production by Stimulated Blood Mononuclear Cells

Abstract: Increased total serum IgE is observed in alcoholics together with a paradoxically low ratio of Th2 to Th1 cytokine production by phytohemagglutinin-stimulated PBMCs. These findings are independent of the atopic status of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 44 publications
6
73
1
Order By: Relevance
“…Likewise, it has been shown that ethanol-related IgE increase is independent of associated habits such as smoking, both in alcoholics and in a defined healthy population (González-Quintela et al, 2000). From this data it may be hypothesized that IgE increases in alcoholics might be due to alcohol and its metabolites per se, which would mean that alcohol could act as an additional antigen or allergen (Domínguez-Santalla et al, 2001). …”
Section: Ethanol and Humoral Immunitymentioning
confidence: 99%
“…Likewise, it has been shown that ethanol-related IgE increase is independent of associated habits such as smoking, both in alcoholics and in a defined healthy population (González-Quintela et al, 2000). From this data it may be hypothesized that IgE increases in alcoholics might be due to alcohol and its metabolites per se, which would mean that alcohol could act as an additional antigen or allergen (Domínguez-Santalla et al, 2001). …”
Section: Ethanol and Humoral Immunitymentioning
confidence: 99%
“…The interaction between alcohol and the immune system is very complex (29,30). Modification of a diversity of immune responses may be involved, such as loss of natural killer cell activity (31), changes in immunoglobulins (32,33,34), and altered cytokine production (32). Moreover, human studies of high alcohol intake individuals as well as animal studies have revealed alterations in both Th1-and Th2-mediated immunity (35).…”
Section: Alcohol and Autoimmunitymentioning
confidence: 99%
“…Evidence that EtOH polarizes the immune response toward Th2-driven humoral immunity is reported in alcoholics (25). We hypothesize that phenotypical and functional changes induced by in vitro EtOH exposure ofcontrol iDCs, even though quantitatively small, together with other possible ethanol-induced DC changes, may be responsible for the observed Th2 cell polarization.…”
Section: Discussionmentioning
confidence: 93%